Stereoselective one-pot synthesis of β-alkylsulfide enol esters. Base-triggered rearrangement under mild conditions - Heredia, Adrián Alberto (2014)
A stereoselective one-pot procedure was developed to prepareS-substituted (Z)-enol esters through abase-triggered rearrangement. This transition metal-free multicomponent approach can be performedunder an air atmosphere at room temperature, tolerates a wide set of chemical functionalities and gener-ally affords high isolated yields. The (Z)-selectivity arises from the [1,4]-S-toO-acyl migration.